1998
DOI: 10.1046/j.1365-2133.1998.02072.x
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of the influence of season (cold and dry air) on the occurrence of irritant skin changes of the hands

Abstract: In the course of an ongoing cohort study on constitutional and occupational risk factors for the development of irritant hand dermatitis in hairdressing apprentices, an increased prevalence of irritant skin changes was noted in a subgroup examined during particularly cold winter months. Prompted by this observation, the importance of several meteorological factors (day means of temperature, relative and absolute humidity) was assessed in extensive statistical analyses based on data of 742 participants, supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
86
2
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 13 publications
9
86
2
5
Order By: Relevance
“…Point and period prevalences of the outcome of interest in both cohorts are shown in table 1, together with the respective incidence rates relating new occurrences to the cumulated person-time at risk of the study participants. Analyses of the office cohort (9) and the hairdressing cohort (6,7,11) have been published previously; the following paper will focus on a comparison between the 2 cohorts based on prevalence data at the stage of final follow-up, employing a multifactorial analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Point and period prevalences of the outcome of interest in both cohorts are shown in table 1, together with the respective incidence rates relating new occurrences to the cumulated person-time at risk of the study participants. Analyses of the office cohort (9) and the hairdressing cohort (6,7,11) have been published previously; the following paper will focus on a comparison between the 2 cohorts based on prevalence data at the stage of final follow-up, employing a multifactorial analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Low ambient absolute humidity had been found to be significantly associated with the occurrence of irritant skin changes of the hands in a previous analysis of 2 hairdressing subcohorts (7). Thus relevant meteorological parameters were obtained from the German Meterological Service (Deutscher Wetterdienst) for inclusion in the multivariate analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that skin condition worsens after exposure to low humidity 7,8) , and that this is usually observed in seasons in which heating is used. In a Swedish study that examined seasonal variation in unspecific symptoms, however, the prevalence of most symptoms did not differ much throughout the four seasons 9) .…”
mentioning
confidence: 99%